Community Entrepreneurship: A Social Approach in Managing Business among Women in East Java - Winarno, Agung; Agustina, Yuli; Narmaditya, Bagus Shandy (Hong Kong Journal of Social Sciences, 2022)
Tackling poverty and enhancing community welfare have been concerns in the Indonesian government. Community entrepreneurship offers the opportunity for the community to obtain better economic welfare. This study aims to examine the implementation of community entrepreneurship in Indonesia and propose a model enhancing community well-being. This study adopted a qualitative method with a case study approach at Pelangi Nusantara in Malang, East Java, Indonesia, to reach comprehensive findings of this phenomenon. This study involved community members using in-depth interviews and documentation in gathering the data. The findings indicate that the establishment of community entrepreneurship was initiated by the same willingness among members to enhance their household welfare. Additionally, community empowerment can be an alternative for women and housewives to obtain an additional income to support their families. Lastly, the holistic model of empowerment can promote better community entrepreneurship. Keywords: community entrepreneurship, community welfare, household well-being, entrepreneurial activities.